Sistem Informasi Sekolah dan Pendaftaran Siswa Baru Berbasis Web pada SMA N 1 Baturetno - Padwa, Fisa Iriana; , Yusuf Sulistyo N., ST., M.Eng (2016)
The development of increasingly rapid technological provides effectiveness in the good life for humans. With the development of computer technology, smartphones, and Internet public can find information from anywhere in the world without being obstructed by the distance of time and place. With these considerations needed a system to facilitate access to school information and registration process for prospective students or parents guardian. This is an important concern for SMA N 1 Baturetno and hope for parents or guardians of prospective students in order to facilitate the partial or total consideration in the process of registration to school. Based on this background, the author makes the School of Information Systems and New Student Registration Web Based on SMA N 1 Baturetno easily accessible. Create websites easier and more convenient to use on the device browser and technologies that exist today, such as Tab, Smartphone. The programming language used is PHP MySQL database on XAMPP, editor Notepad ++ and Ajax and Jquery.